2005
DOI: 10.1057/palgrave.emr.1500023
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and relationships: when cooperation is the norm

Abstract: We believe that structural changes in a knowledge economy mean that managers will increasingly seek to make cooperative relationships the norm in their organisations. However, they are hampered in their attempts to do so by organisation designs that institutionalise the dominant assumption about human intentionality, which sees people and their relationships as motivated by self‐interest. We argue that the self‐interest assumption runs counter to the types of cooperation required to leverage fully the potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 50 publications
0
45
0
Order By: Relevance
“…This is the case of the design of compensation policies that reward group performance and cooperative behaviors (Leana and Van Buren, 1999;Nahapiet et al, 2005), organization designs that encourage the formation of networks (Nahapiet et al, 2005), reconsidering physical layout of buildings to encourage informal connections (Brown and Duguid, 2001;Fairtlough, 1994), or rules and procedures that promote stability (Cohen and Prusak, 2000;Leana and Van Buren, 1999). In this respect, Wimbush and Shepard (1994) found that employees in firms characterized by ethical norms and rules exhibit greater proclivity to behave ethically than in instrumental work contexts.…”
mentioning
confidence: 96%
“…This is the case of the design of compensation policies that reward group performance and cooperative behaviors (Leana and Van Buren, 1999;Nahapiet et al, 2005), organization designs that encourage the formation of networks (Nahapiet et al, 2005), reconsidering physical layout of buildings to encourage informal connections (Brown and Duguid, 2001;Fairtlough, 1994), or rules and procedures that promote stability (Cohen and Prusak, 2000;Leana and Van Buren, 1999). In this respect, Wimbush and Shepard (1994) found that employees in firms characterized by ethical norms and rules exhibit greater proclivity to behave ethically than in instrumental work contexts.…”
mentioning
confidence: 96%
“…This implies that as an economy develops, organizations come closer together to synergize their efforts and capabilities. This occurs both at intra-organizational (Nahapiet, Gratton & Rocha, 2005) and inter-organizational (Miles, Miles & Snow (2005); Rocha, 2006) levels.…”
Section: Theory Vs Practicementioning
confidence: 99%
“…The objective of this paper is to address this gap by arguing that HR practices may influence employee knowledge sharing attitudes and behaviour through their impact on perceptions of an organisational social climate conducive to cooperative social relations and teamwork orientation. Such a climate has been identified in the literature as key to knowledge exchange and organisational learning (Nahapiet, Gratton, & Rocha, 2005;Jackson, Chuang, Harden, & Jiang, 2006).…”
Section: Introductionmentioning
confidence: 99%